2016
DOI: 10.3390/s16050697
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Moisture in Wood for Application in the Restoration of Old Buildings

Abstract: There are many historic buildings whose construction is based on timber frame walls. Most buildings built during the nineteenth and early twentieth centuries were based on timber frame walls with vertical support elements. These timber frame elements are affected by their moisture content and by the passage of time. If the interaction of the timber frame walls with hygrothermal fluctuations were known, the maintenance of these buildings could be improved significantly. To determine the moisture content of wood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In this field of material moisture measure, capacitive sensors are very well accepted due to their easy fabrication, application, and low cost compared to other typologies. Some authors showed that application range of these sensors can be very wide, around 175–625 ppm [21], enabling their application in different materials; e.g., measurement of the moisture level and degradation of wood [22] and moisture content measurement in gases using high linearity in the capacitive sensors’ response [23]. This ideal/linear response is not always possible to obtain; such is the case with some strain sensors used to measure deformations and study material microstructure [24], whose response should be studied and improved to be interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…In this field of material moisture measure, capacitive sensors are very well accepted due to their easy fabrication, application, and low cost compared to other typologies. Some authors showed that application range of these sensors can be very wide, around 175–625 ppm [21], enabling their application in different materials; e.g., measurement of the moisture level and degradation of wood [22] and moisture content measurement in gases using high linearity in the capacitive sensors’ response [23]. This ideal/linear response is not always possible to obtain; such is the case with some strain sensors used to measure deformations and study material microstructure [24], whose response should be studied and improved to be interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the uncertainty of the presented method can be deduced from comparison with other authors. Some of them, e.g., Fernandez-Golfin et al [30] and Moron et al [31], developed similar circuits and calibrated them with laboratory methods. Fernandez-Golfin et al [30] predicted the moisture content of wood with an error ±1.0%.…”
Section: Discussionmentioning
confidence: 99%
“…They also revealed that the measuring direction has negligible influence (error of estimation <±0.5%) on moisture content estimates, below the moisture content of about 15%. Moron et al [31] compared results of moisture content measurement conducted by their capacitance meters with those based on the variation of electromagnetic transmittance of timber. They reported similar accuracy (below 1%) between both methods in measurement range 1 MΩ to 100 GΩ.…”
Section: Discussionmentioning
confidence: 99%
“…GPR experiments are then repeated at different humidity levels. Humidity by mass water (%) is calculated by adopting the following expression (Moron et al, 2016):…”
Section: Methodsmentioning
confidence: 99%